Clear or Confusing? Investigating Pronunciation Challenges Among Young EFL Learners in Southern Thailand - Urona, Dara; Husna, Faizatul; Juliana, Rena; Lemsoh, Subaidah (ELLITE: Journal of English Language, Literature, and Teaching, 2025)
This study seeks to explore the pronunciation difficulties encountered by students at Tessaban 2 Ban Sadao School in Thailand. Utilizing qualitative research methodologies, which include pronunciation evaluations and semi-structured interviews with educators, the research aims to identify prevalent pronunciation mistakes and analyze the instructional strategies employed by teachers. The results indicate that students face challenges with particular phonemes, such as /r/, /v/, /ʃ/, and final consonant clusters, primarily influenced by their first language (L1). Furthermore, issues related to incorrect word stress and unsuitable intonation patterns impede clarity and understanding in spoken communication. Educators implement a variety of techniques, such as phonetic training, minimal pair exercises, and imitation practices, to help students enhance their pronunciation skills. Nevertheless, the limited exposure to authentic English language contexts continues to pose a significant obstacle. This research highlights the critical need for a stronger focus on pronunciation within the English language curriculum, as well as the importance of providing students with increased opportunities to interact with genuine English-speaking environments. By tackling these challenges, educators can formulate more effective and targeted teaching strategies, ultimately improving the pronunciation and communication abilities of EFL (English as a Foreign Language) learners in Thailand.